Modified carbon paste electrode for the electrochemical sensing of 3,5,6-trichloro-2-pyridinol - Santos, A. L. d. [UNESP]; Batista, Elisete A. [UNESP]; Gonçalves, Luís Moreira; Sotomayor, Maria del Pilar T. [UNESP] (Taylor & Francis, 2017)
An electrochemical sensor for the determination of 3,5,6-trichloro-2-pyridinol (TCP), the main metabolite of the pesticide chlorpyrifos, was herein developed. TCP has greater solubility than the source pesticide, and its occurrence in ground and surface water is more frequent and more dangerous. The sensor was fabricated using carbon paste modified with the inorganic complex chloro-5,10,15,20-tetrakis-(pentafluorophenyl)-21 H,23 H-porphyrin iron(III) (FeTPPCl); this metallic complex has a chemical core structure similar to the heme cofactor of the cytochrome P450 (CYPs). Measurements were performed with square-wave voltammetry. Using the optimised voltammetric parameters and without any sample preparation, the sensor showed a limit of detection of 2.8 mg L−1 (14 μmol L−1), recoveries ca. 102%, suitable selectivity and long durability (over 1 month).
Keywords: Biomimetic sensor; electroanalysis; insecticide; Iron porphyrin complex; modified carbon paste electrode